Improving Early Childhood Prosocial Behavior through Activity Storytelling with Puppets - Ika Tyas Mustika Sari; Hapidin Hapidin; Yuliani Nurani (LPPM Universitas Pahlawan Tuanku Tambusai, 2018)
The purpose of this study is to describe the process and learning outcomes through the activities of storytelling with puppets that can improve the prosocial behavior of the children in Kindergarten group A, Global Persada Mandiri School, Bekasi, in the academic year 2017/2018. Research subjects of this action are 14 children aged 4-5 years. This research method is action research which refers to the research of Kemmis MC Taggart which consist of planning, action and observation stage, then reflection. This study consists of 2 cycles, each cycle consisting of 8 meetings. Data analysis technique used in this research is quantitative and qualitative. Quantitative data analysis with statistical descriptions is comparing the results obtained from the pre-action, the first cycle to the second cycle. Qualitative data analysis is done by analyzing data of field record, interview record and documentation record by reducing data, display data and make a conclusion. The results of this study indicate that there is an increase in the behavior of child prosocial through the storytelling activity with puppets, can be proved by the average acquisition of TCP (Level of Development Achievement) in one class at pre-action of 17,7, and increased in the second cycle of 37.5